2013
DOI: 10.1155/2013/723168
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia with Propofol versus Sevoflurane: Does the Longer Neuromuscular Block under Sevoflurane Anesthesia Reduce Laryngeal Injuries?

Abstract: Anesthesia can be maintained with propofol or sevoflurane. Volatile anesthetics increase neuromuscular block of muscle relaxants. We tested the hypothesis, that sevoflurane would cause less vocal cord injuries than an intravenous anesthesia with propofol. In this prospective trial, 65 patients were randomized in 2 groups: SEVO group, anesthesia with sevoflurane, and TIVA group, total intravenous anesthesia with propofol. Intubating and extubating conditions were evaluated. Vocal cord injuries were examined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…It has been reported that postoperative ketorolac is mostly used in patients with sore throat. Mencke et al compared sevoflurane inhalation anesthesia and TIVA with propofol and found the incidence of postoperative sore throat to be 10% in the TIVA Group (20). However, they did not compare this incidence in terms of sore throat severity as in our study.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…It has been reported that postoperative ketorolac is mostly used in patients with sore throat. Mencke et al compared sevoflurane inhalation anesthesia and TIVA with propofol and found the incidence of postoperative sore throat to be 10% in the TIVA Group (20). However, they did not compare this incidence in terms of sore throat severity as in our study.…”
Section: Discussioncontrasting
confidence: 68%
“…In iv techniques, careful titration of these drugs must ensure adequate depth of anesthesia. The intermittent bolus administration of fentanyl may result in unstable states of consciousness during surgery compared to continuous remifentanil infusion (20). Insufficient relaxation or movement due to inadequate depth of anesthesia can also contribute to increased sore throat (9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhalation anesthesia was not adopted in this study, because inhalation anesthesia was found that it can increase the incidence and duration of neuromuscular blockade after surgery. [18] Body weight can also change the distribution volume of neuromuscular blocking in the body, AChE activity, and so on, thereby affecting the muscle relaxation effect. [19] In this study, patients with a body mass index greater than 30 kg/m 2 were excluded from the study.…”
Section: Discussionmentioning
confidence: 99%